Boricua pop : Puerto Ricans and the latinization of American culture - Negrón-Muntaner, Frances (Sexual cultures., 2004)
Boricua Pop is the first book solely devoted to Puerto Rican visibility, cultural impact, and identity formation in the U.S. and at home. Frances Negrón-Muntaner explores everything from the beloved American musical West Side Story to the phenomenon of singer/actress/ fashion designer Jennifer Lopez, from the faux historical chronicle Seva to the creation of Puerto Rican Barbie, from novelist Rosario Ferré to performer Holly Woodlawn, and from painter provocateur Andy Warhol to the seemingly overnight success story of Ricky Martin. Negrón-Muntaner traces some of the many possible itineraries o.